(untitled) (Applied Biological Research, 2018)
In present study various physicochemical constituents of organically and conventionally grown kale (Brassica oleraceae L. var. acephala) were studied. The proximate constituents were determined by standard methods. The results revealed that dry matter, crude protein, crude fat, ash and total carbohydrate content in organically and conventionally grown kale were 12.15, 3.54, 0.68, 2.11 and 6.09 and 10.60, 2.66, 0.53, 1.63 and 5.78%, respectively. The total sugars, reducing sugar and ascorbic acid contents in organically grown kale were 1.95%, 1.05%, 49.0 mg 100 g-1 as compared to 1.87%, 1.02% and 44.0 mg 100 g-1, respectively, in conventionally grown kale. The sodium and potassium contents were high in organically grown kale. Kale grown with organic inputs was found nutritionally superior to conventionally grown kale so can be incorporated in food formulation as therapeutic agent.